Adat Palai Ngandi di Kabupaten Sumba Timur di Tinjau dari Undang-undang Perkawinan - Umbu Rendhy Ahadie Ndjurumbaha; I Made Suwitra; Ida Ayu Putu Widiati (Fakultas Hukum, Universitas Warmadewa, 2021)
The custom of Palai Ngandi (elopement) that occurs in East Sumba, East Nusa Tenggara is a social gap because couples who elope do not notify the woman's parents to marry. The purpose of this study is to analyze the recognition of the Palai Ngandi custom in East Sumba and the legal consequences of implementing the Palai Ngandi in Law Number 1 of 1974 in conjunction with Law Number 16 of 2019. The method used in this study is empirical research with a statutory approach, the customary law approach, the concept approach, the legal sociological approach and the case approach. The technique of collecting legal materials is carried out by observation and conducting a literature review to obtain primary and secondary legal materials which are then analyzed using descriptive analysis techniques. The results of the study show that there are still many Palai Ngandi customs in Pandawai District, East Sumba Regency. The Palai Ngandi custom which is a form of this gap has caused several consequences for the perpetrators and the parents of both parties which are resolved by existing customs in the community so that a good middle point can be found between the two parties who carry out Palai Ngandi.